دور الاتفاقيات التجارية الجزائرية في تنويع الصادرات خارج المحروقات - فؤاد،هرشة; محمد يزيد،خضير; اعماره،بجاق; أحمد،قاسمي (university of eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى إبراز دور الاتفاقيات التجارية الجزائرية في تشجيع الصادرات خارج المحروقات خلال الفترة 2000 إلى 2022 ، حيث تم تحديد أهم النصوص التي جاءت بهذه الاتفاقيات ودخولها حيز التطبيق، بالإضافة إلى دراسة القدرة التنويعية للتصدير للدولة خلال فترة الدراسة . وقد تما لتوصل إلى أن الجزائر لم تصل إلى الأهداف المرجوة ، ولم يتم الاستغلال الجيد لمزاياها في الفترة الممتدة من2000 إلى 2019 ، أما بعد 2019 فقد تم انتهاج دبلوماسية اقتصادية رشيدة ، مما أدى إلى تحقيق جزء كبير من الأهداف المرجوة حيث وصل الناتج المحلي الإجمالي إلى 187.2 مليار دولار عام 2022، وقيمة الصادرات خارج المحروقات وصلت إلى ما يفوق 7 مليار دولار . This study aims to highlight the role of Algerian trade agreements in encouraging exports outside of hydrocarbons during the period 2000 to 2022, as the most important texts that brought about these agreements and their entry into force were identified, in addition to studying the country’s export diversification capacity during the study period. It was concluded that Algeria did not reach the desired goals, and its advantages were not well exploited in the period extending from 2000 to 2019. However, after 2019, rational economic diplomacy was pursued, which led to achieving a large part of the desired goals, as the gross domestic product reached 187.2. One billion dollars in 2022, and the value of exports outside of fuel reached more than 7 billion "
مذكرة ماستر علوم تجارية
Keywords: الاتفاقيات التجارية ، التنوع الاقتصادي ، الجزائر ، الصادرات خارج المحروقات ، التصدير . : trade agreements; economic diversification; Algeria; exports outside of hydrocarbons; export.